SYNCHRONIZATION OF OVULATION IN REPEAT BREEDING CROSSBRED COWS - Vijayarajan, A; Chandrahasan, C; Napolean , R Ezakial (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Ovulation was synchronized (Ovsynch) in 10 crossbred cows using Gonadotropin Releasing Hormone (GnRH) and Prostaglandin F2α (PGF2α) and the animals were inseminated at a fixed time. Another 10 cows served as control and were inseminated at detected estrus. The percentage of induced estrus was 100 per cent. The first service conception rate obtained for ovsynch group was higher than the control group (50 Vs 20 per cent). The overall conception rate was also higher for ovsynch group when compared with the control group (60 Vs 20 per cent). Synchronization of ovulation had improved the conception rate in repeat breeding crossbred cows.
Keywords: GnRH; Mid heat; Artificial Insemination; Conception rate; Repeat breeding cows